Molecular characterization of PH-negative myeloproliferative neoplasms in Ukraine - Mishcheniuk, O.Y.; Kostukevich, O.M.; Dmytrenko, I.V.; Sholoyko, V.V.; Prokopenko, I.M.; Martіna, Z.V.; Pilipenko, G.V.; Klymenko, S.V. (Experimental Oncology, 2013)
Aim: The aim of this study was to examine the JAK2 V617F, the G1691A allele of factor V, and the G20210A prothrombin gene mutation status, and their predictive value for thrombosis in patients with Ph-negative myeloproliferative neoplasms (MPN) in Ukraine, with special emphasize to patient exposed to ionizing radiation due to the Chernobyl accident. Materials and Methods: There were 198 patients with Ph-negative MPN included in the study. Of these, 45 patients had experienced radiation exposure due to the Chernobyl accident. The JAK2 V617F mutation, the G1691A of factor V and the G20210A of prothrombin were detected by allele-specific polymerase chain reaction. Results: The polycythemia vera and essential thrombocythemia patients in unexposed group and Chernobyl patients were comparable in terms of the JAK2 V617F mutation prevalence with the frequency of anomaly corresponding well to the published data on unselected cases of these types of Ph-negative MPN. The JAK2 V617F mutation was less common on the border of statistical significance (p = 0.08) in Chernobyl primary myelofibrosis (PMF) patients than in non-exposed patients. JAK2 V617F positive patients had higher level of leukocytes (p = 0.03), hemoglobin (p =0.04) and splenomegaly (p = 0.04) than those without mutation. The JAK2 V617F mutation was strong predictor for thrombosis in essential thrombocytemia patients (relative risk=3.1, 95% CI = 1.7–16.4, p = 0.03). In PMF, the association with thrombosis was found for the G1691A allele of factor V (p = 0.03). The risk of thrombosis associated with the inherited thrombophilia in PMF patients was 7.0-fold (95% CI = 1.41–33.1, p = 0.03) higher than in polycythemia vera patients. The inherited thrombophilia increased risk of thrombotic complication 5.4-fold (95% CI = 1.41–18.17, p = 0.01) in overall cohort of Ph-negative myeloproliferative neoplasms patients. This trend continued in Chernobyl patients (p = 0.02), but not in unexposed cases. Conclusions: Our findings confirm previous results of other studies reporting that the JAK2 V617F mutation signiﬁcantly and independently inﬂuences on a disease phenotype in Ph-negative MPN. The inherited thrombophilia is important risk factors of the thrombosis development in overall cohort primary myelofibrosis patients, and especially in disease developed following radiation exposure.